ORGANIZATION OF THE ECOLOGICAL ENVIRONMENT IN PRESCHOOL EDUCATION - Raximbayeva, Aziza (Журнал иностранных языков и лингвистики, 2021)
At present, there is a deterioration of the ecological situation in the world due to the influence of techno genic factors, many of which have a detrimental effect on the environment. The negative aspects of the problem of human relations with the environment can be resolved only if the quality of the ecological education of the population, its ecological culture and upbringing, and the implementation of the principles of moral and sustainable development are improved. The process of realizing the need to change the life paradigm should take place as soon as possible, until nature has lost the ability to adapt to the consequences of the development of civilization, until natural resources have dried up and irreversible environmental disasters have not occurred.